Desnutrición en gestantes de 19 semanas - Jaramillo Guerrero, Anabel Carolina (2020)
Among the important elements for the development of a country is health, especially that of pregnant women as they are a vulnerable group. The weight of the newborn is linked to the nutritional status of the pregnant woman, compromising the health of new citizens being critical determinants of the health of the individual in adulthood. Morbidity and mortality in populations, is increased by malnutrition, decreases productive capacity, quality of life, increasing social costs, increasing poverty belts, which affects the population causing inequality and exclusion due to lack of access to health, education, employment, basic sanitation, thus perpetuating the cycle of poverty, hunger and disease or also called malnutrition and poverty. We present the case of a 17-year-old patient with severe thinness and a pregnancy of 19.3 weeks of gestation by ultrasound, who attended the second-level hospital for emergency care with a clinical picture of fever with 14 hours of evolution, pain in the lumbosacral region with 10 hours of evolution, ultrasound scan shows a single transverse live product with a fcf of 15 bpm. after 3 hours it is re-evaluated with signs of pa: 91/55 mmhg, fc 102 bpm, t 37.5 ° c sat 98%, fr 20 rpm, therefore admission is indicated.